Seventh United Nations Survey of Crime Trends and Operations of Criminal Justice Systems, covering the period 1998 - 2000 (PDF, 3.2 Mb) - (:unkn) unknown (My University, 2016)
The major goal of the United Nations Surveys on Crime Trends and the Operations of Criminal Justice Systems is to collect data on the incidence of reported crime and the operations of criminal justice systems with a view to improving the analysis and dissemination of that information globally. The survey results provide an overview of trends and interrelationships between various parts of the criminal justice system to promote informed decision-making in administration, nationally and internationally.